A new terrain of struggle : the liberation of the 'self' : an analysis of the narratives of the experiences of activists of the Mass Democratic Movement (MDM) about their circumstances in post-apartheid South Africa, in the context of reconciliation - Swarts, Brigitte Stephanie (Department of Psychology, 2014)
Includes bibliographical references (leaves 138-145).